2022
DOI: 10.3390/biology11071028
|View full text |Cite
|
Sign up to set email alerts
|

Dissection of Paenibacillus polymyxa NSY50-Induced Defense in Cucumber Roots against Fusarium oxysporum f. sp. cucumerinum by Target Metabolite Profiling

Abstract: To gain insights into the roles of beneficial PGPR in controlling soil-borne disease, we adopted a metabolomics approach to investigate the beneficial impacts of P. polymyxa NSY50 on cucumber seedling roots under the pathogen of Fusarium oxysporum f. sp. cucumerinum (FOC). We found that NSY50 pretreatment (NSY50 + FOC) obviously reduced the production of reactive oxygen species (ROS). Untargeted metabolomic analysis revealed that 106 metabolites responded to NSY50 and/or FOC inoculation. Under FOC stress, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 95 publications
0
1
0
Order By: Relevance
“…Studies have shown that glucose is utilized as a substrate for glycolysis and is beneficial for improving plant metabolism and stress resistance (Du et al, 2022). In our study, glycolysis was active during recovery, yet the amount of glucose increased, which may be due to the increase in photosynthesis during recovery.…”
Section: Dynamic Changes In Glycolysis Promote Energy Production In N...mentioning
confidence: 49%
“…Studies have shown that glucose is utilized as a substrate for glycolysis and is beneficial for improving plant metabolism and stress resistance (Du et al, 2022). In our study, glycolysis was active during recovery, yet the amount of glucose increased, which may be due to the increase in photosynthesis during recovery.…”
Section: Dynamic Changes In Glycolysis Promote Energy Production In N...mentioning
confidence: 49%